2013
DOI: 10.1371/journal.pone.0063049
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Domain of Sortilin Interacts with Amyloid Precursor Protein and Regulates Its Lysosomal and Lipid Raft Trafficking

Abstract: The processing of Amyloid precursor protein (APP) is multifaceted, comprising of protein transport, internalization and sequential proteolysis. However, the exact mechanism of APP intracellular trafficking and distribution remains unclear. To determine the interaction between sortilin and APP and the effect of sortilin on APP trafficking and processing, we studied the binding site and its function by mapping experiments, colocalization, coimmunoprecipitation and sucrose gradient fractionation. We identified fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…The S825 phosphomimetic activated TNAP activity through TGN localization, while the phosphor-null variant localized to lysosomes. These data agree with previous findings that TNAP activation occurs in the early secretory pathway and subsequently moves and localizes to the plasma membrane (26) and that the sortilin intracellular domain controls the fate of interacting partners from the lysosomes to lipid rafts (47). The p825 site enhances the binding of sortilin-to-Golgi-associated, γ-adaptin ear-containing, ARF-binding protein (GGA) -cytosolic adaptors mediating the sorting of transmembrane proteins (48).…”
Section: Discussionsupporting
confidence: 92%
“…The S825 phosphomimetic activated TNAP activity through TGN localization, while the phosphor-null variant localized to lysosomes. These data agree with previous findings that TNAP activation occurs in the early secretory pathway and subsequently moves and localizes to the plasma membrane (26) and that the sortilin intracellular domain controls the fate of interacting partners from the lysosomes to lipid rafts (47). The p825 site enhances the binding of sortilin-to-Golgi-associated, γ-adaptin ear-containing, ARF-binding protein (GGA) -cytosolic adaptors mediating the sorting of transmembrane proteins (48).…”
Section: Discussionsupporting
confidence: 92%
“…Because the APP motives in its luminal and CT domains implicated in sortilin binding are either identical or similar in APLP2 (not shown), this suggests that sortilin may also bind APLP2 via these motives and regulate its trafficking. Interestingly, sortilin was shown to target APP for lysosomal degradation (55), whereas our data revealed that sortilin stabilizes APLP2 (Fig. 4B), suggesting a functional difference between the interaction of sortilin with APP or APLP2.…”
Section: Discussionmentioning
confidence: 62%
“…It was shown that sortilin and the amyloid precursor protein (APP) bind to each other via luminal (head-to-head) and cytosolic (tail-to-tail) interaction domains (55). Their cytosolic tails interact via the FLVHRY motif of sortilin with the YNPTYKFFE motif in APP, which overlaps with the ARH binding consensus YENPTY (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…) and negatively regulates APP lipid raft targeting (Yang et al . ). Furthermore, sortilin interacts with p75 NTR to induce neuronal apoptosis and increase AD severity (Skeldal et al .…”
mentioning
confidence: 97%